Molecular mechanisms of ferroptosis and the potential therapeutic targets of ferroptosis signaling pathways for glioblastoma - Zhang, Meng; Lei, Qian; Huang, Xiaobo; Wang, Yi (Frontiers in Pharmacology, 2022)
Ferroptosis is a new programmed cell death pathway proposed in 2012, and the findings were published in the journal Cell that year. Ferroptosis is a new form of cell death different from autophagy, apoptosis and necrosis, and its molecular characteristics include iron-dependent accumulation of lipid reactive oxygen species, changes in mitochondrial morphology, and membrane permeability damage, which are associated with multiple are closely related to various human diseases, especially tumors of the nervous system. Glioblastoma is the most common primary malignant tumor of the adult central nervous system, and the 5-year survival rate is only 4%-5%. This study reviewed the role and mechanism of ferroptosis in glioblastoma, as well as the research status and progress of ferroptosis as a potential therapeutic target. The mechanism of ferroptosis is related to the level of intracellular iron metabolism, lipid peroxide content and glutathione peroxidase 4 activity. It is worth exploring how ferroptosis can be applied in treatment, but the research on how ferroptosis is related to other apoptosis methods and how to apply ferroptosis to drug-resistant tumors is not enough. Ferroptosis is a promising therapeutic target for glioblastoma. In-depth study of its mechanism of action in glioblastoma and its application in clinical treatment is expected to provide new insights for glioblastoma patients.